1984
DOI: 10.1136/jnnp.47.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory failure as initial symptom of acid maltase deficiency.

Abstract: , during the period 1970-1982. Five of these patients developed respiratory failure, and in four this was the initial symptom. The occurrence of respiratory failure as an early symptom of this muscular disease is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
5

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 10 publications
0
22
0
5
Order By: Relevance
“…Although the pattern of muscle weakness is variable, a rough correlation has been observed between measures of pulmonary function and proximal muscle weakness, particularly in the lower extremities 47. Diaphragmatic involvement can be an early and prominent finding in Pompe disease and respiratory failure often develops while patients are still ambulatory; it may even be the initial clinical manifestation of the disease 35,46,48–50. Diaphragm weakness may be characterized by a decrease in the vital capacity (VC) while the patient is in the supine versus prone position (a 10% decrease in VC indicates diaphragmatic weakness; a 30% decrease indicating severe weakness) 50.…”
Section: Pulmonarymentioning
confidence: 99%
“…Although the pattern of muscle weakness is variable, a rough correlation has been observed between measures of pulmonary function and proximal muscle weakness, particularly in the lower extremities 47. Diaphragmatic involvement can be an early and prominent finding in Pompe disease and respiratory failure often develops while patients are still ambulatory; it may even be the initial clinical manifestation of the disease 35,46,48–50. Diaphragm weakness may be characterized by a decrease in the vital capacity (VC) while the patient is in the supine versus prone position (a 10% decrease in VC indicates diaphragmatic weakness; a 30% decrease indicating severe weakness) 50.…”
Section: Pulmonarymentioning
confidence: 99%
“…Respiratory failure has been found in about one third of patients with late-onset Pompe's disease [2,5,6]. In a recent questionnaire study in 54 patients of the Dutch Neuromuscular Diseases Association, registered has having late-onset Pompe's disease, HAGEMANS et al [29] found that 20 patients used ventilatory assistance, having started at a mean age of 49 yrs, and that 23 patients used a wheelchair, starting at a mean age of 46 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the presenting symptoms and the clinical outcomes in adults seem to vary widely. Although respiratory muscle involvement is rarely inaugural [5,6], it may occur early in the course of the disease and may cause death. These characteristics, and the likelihood that new treatments recently tested in infantile and juvenile Pompe's disease [7][8][9][10] will require evaluation in adult-onset disease, indicate a need for investigations into the relationships between respiratory muscle weakness and weakness in other muscles.…”
mentioning
confidence: 99%
“…Adult GSD II can escape diagnosis if the clinician is not familiar with the various clinical presentations of the disease or has misconceptions regarding the various diagnostic procedures that should be performed [10]. Patients with adult GSD II may also escape diagnosis when they present with acute respiratory insufficiency as their first clinical symptom [18]. …”
Section: Discussionmentioning
confidence: 99%